Nitazoxanide and tizoxanide demonstrate high levels of in vitro activity against metronidazole-susceptible and metronidazole-resistant Trichomonas vaginalis clinical isolates - Keonte J. Graves; John C. Williamson; Jan Novak; Hemant K. Tiwari; W. Evan Secor; Christina A. Muzny (Microbiology Spectrum)
ABSTRACT Trichomonas vaginalis is the most common non-viral sexually transmitted infection worldwide. We compared the in vitro activity of the thiazolide nitazoxanide (NTZ) and its metabolite, tizoxanide (TIZ), with the activity of the Food and Drug Administration-approved 5-nitroimidazoles (metronidazole [MTZ], tinidazole [TDZ], and secnidazole [SEC]) against MTZ-susceptible and MTZ-resistant Trichomonas vaginalis clinical isolates. Frozen, stored T. vaginalis clinical isolates (n = 36) were cultured in Diamond’s trypticase-yeast-maltose media supplemented with heat-inactivated horse serum and an antibiotic cocktail. Drug-susceptibility assays for the thiazolides (NTZ and TIZ) and the 5-nitroimidazoles (MTZ, TDZ, and SEC) were performed to determine the minimum lethal concentrations (MLCs) for each T. vaginalis isolate and the median MLC for each drug. Of the 36 T. vaginalis isolates cultured, 18 were MTZ resistant and 18 were MTZ susceptible. For the 18 MTZ-resistant strains, the median MLCs for MTZ, TDZ, and SEC were 100, 25, and 50 µg/mL, respectively. By contrast, the median MLCs for NTZ and TIZ were considerably lower at 1.6 and 0.8 µg/mL, respectively. The similarity in thiazolide MLCs in all T. vaginalis strains, regardless of sensitivity to MTZ, suggests that NTZ and TIZ act via a different mechanism than the 5-nitroimidazoles. Future investigations will focus on the in vivo activity of NTZ and TIZ as well as the efficacy of thiazolides used as monotherapy or as combination therapy, particularly in T. vaginalis-infected patients who do not respond to 5-nitroimidazole treatment.IMPORTANCEInvestigating drug resistance and alternative treatment options for Trichomonas vaginalis is crucial due to the increasing prevalence of persistent infections and the potential failure of standard therapies (i.e., 5-nitroimidazoles). Trichomoniasis can lead to significant health complications, including increased susceptibility to sexually transmitted infections and adverse pregnancy outcomes. The rise of 5-nitroimidazole drug-resistant strains poses a challenge to effective treatment, necessitating ongoing research to understand the mechanisms behind this resistance. Exploring alternative treatments, such as novel pharmacological agents like nitazoxanide and tizoxanide, could provide more effective options for managing these persistent infections. Additionally, comprehensive investigations can help inform public health strategies and reduce transmission rates. Ultimately, prioritizing research in this area is essential for improving patient outcomes and safeguarding reproductive health.